2019
DOI: 10.6002/ect.2016.0135
|View full text |Cite
|
Sign up to set email alerts
|

HLA Genotypes in Turkish Hematopoietic Cell Recipients and Likelihood of Finding a Matched Donor Through Family Searches

Abstract: Objectives: Allogeneic hematopoietic stem cell transplant is a life-saving treatment, but donor numbers in Turkey do not meet the increasing demand for this procedure. Here, our objectives were (1) to assess the frequency of HLA-matched related donors in the Turkish population and (2) to identify the HLA antigens and haplotypes that are most frequent in Turkey. Materials and Methods: The HLA genotypes of 841 consecutive recipients and 3071 family members were retrospectively reviewed. Results: Matched related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…Our study showed that about one‐third of the patients with sibling donors found 0/6 antigen‐mismatched or 0/8 allele‐mismatched donors. This availability was comparable to those reported in western cohorts and apparently lower than those in Middle‐Eastern cohorts, which consist of communities with larger families. Because family size is shrinking and we could expect to find fewer HLA‐matched donors with fewer sibling donor‐candidates, the chances of finding HLA‐matched donors among nonsibling family members should be examined more carefully.…”
Section: Discussionsupporting
confidence: 78%
“…Our study showed that about one‐third of the patients with sibling donors found 0/6 antigen‐mismatched or 0/8 allele‐mismatched donors. This availability was comparable to those reported in western cohorts and apparently lower than those in Middle‐Eastern cohorts, which consist of communities with larger families. Because family size is shrinking and we could expect to find fewer HLA‐matched donors with fewer sibling donor‐candidates, the chances of finding HLA‐matched donors among nonsibling family members should be examined more carefully.…”
Section: Discussionsupporting
confidence: 78%
“…The A*02 was the most frequently identified allele, which is consistent with the findings of previous studies. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 The A*24 allele was the second most frequently observed allele. This was finding was consistent with those of most previous studies, except those of the study conducted by Pala et al 7 in the Thracian population.…”
Section: Discussionmentioning
confidence: 97%
“…The allele and some haplotype frequencies of our study were similar to those of most previous studies conducted in our country. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 A comparison of the 8-digit HLA data frequency could not be conducted due to the lack of previous studies reporting the same in our nation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Siblings and offspring of subjects suffering from S are five and four times more likely to develop the disease, respectively [ 75 , 76 , 77 , 78 ]. Different HLA second class (HLA-DR) alleles have been detected to be S-related [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]: HLA DRB1*15 in the Turkish population [ 90 ]; HLADRB1*11 in subjects with extra-pulmonary S [ 91 ]; HLA DRB1*0401 in patients suffering from OS involvement [ 92 ].…”
Section: Literature Reviewmentioning
confidence: 99%